Kendala Pemerintah Dalam Melindungi Hak Atas Keamanan Bagi Konsumen Kuliner Makanan Berbahan Baku Daging Anjing - Elizabeth Putri Sutrisno; Wasis Sugandha (Faculty of Law Universitas Sebelas Maret Surakarta, 2020)
This study aims to find out what are the obstacles of the Surakarta City government especially the Department of Agriculture, Food Security, and Fisheries of Surakarta City in an effort to protect the right to security for consumers of culinary foods made from dog meat in the city of Surakarta. The research method used is socio-legal legal research. Descriptive. This research was conducted by processing primary and secondary data. Primary data obtained by conducting interviews with the Department of Agriculture, Food Security, and Fisheries of the City of Surakarta as well as consumers of food culinary made from dog meat. Whereas secondary data is obtained by conducting a literature study related to existing laws and regulations or research journals. Based on the results of the study, it is known that the Surakarta City Government's obstacle in protecting the right to security for food consumers made from dog meat, especially the Department of Agriculture, Food Security, and Fisheries of Surakarta City is due to several interrelated factors. These factors are legal factors, infrastructure facilities, law enforcement factors, community factors, and cultural factors.Keywords:Food; Consumer; Surakarta.